2022
DOI: 10.1038/s41392-022-01145-1
|View full text |Cite
|
Sign up to set email alerts
|

JMJD family proteins in cancer and inflammation

Abstract: The occurrence of cancer entails a series of genetic mutations that favor uncontrollable tumor growth. It is believed that various factors collectively contribute to cancer, and there is no one single explanation for tumorigenesis. Epigenetic changes such as the dysregulation of enzymes modifying DNA or histones are actively involved in oncogenesis and inflammatory response. The methylation of lysine residues on histone proteins represents a class of post-translational modifications. The human Jumonji C domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 432 publications
0
24
0
Order By: Relevance
“…204,205 It has been reported that JMJD1A can upregulate DCLK1 and CDK6 in a demethylationdependent manner and maintain the occurrence and development of pancreatic cancer. 206,207 The JMJD2 (KDM4) family: The JMJD2 (KDM4) family consists of six proteins (JMJD2A-F), 208,209 all the proteins have the ability to demethylate H3K9me2/me3 and H3K36me2/me3, which are conductive to breast, colorectal, prostate and other cancers formation (Fig. 5).…”
Section: Histone Demethylases (Hdmts)mentioning
confidence: 99%
“…204,205 It has been reported that JMJD1A can upregulate DCLK1 and CDK6 in a demethylationdependent manner and maintain the occurrence and development of pancreatic cancer. 206,207 The JMJD2 (KDM4) family: The JMJD2 (KDM4) family consists of six proteins (JMJD2A-F), 208,209 all the proteins have the ability to demethylate H3K9me2/me3 and H3K36me2/me3, which are conductive to breast, colorectal, prostate and other cancers formation (Fig. 5).…”
Section: Histone Demethylases (Hdmts)mentioning
confidence: 99%
“…Several reports indicate that KDM4 family members are over-expressed in various cancers: KDM4A, KDM4B, and KDM4C are over-expressed in prostate cancer [ 74 ]; amplification of KDM4B is shown in medulloblastoma [ 77 ]; and KDM4C is required for the growth of breast carcinoma [ 78 ] and diffuse large B cell lymphoma [ 79 ]. These family members are involved in diverse biological pathways linked to cancer such as Akt-mTOR signaling for KDM4A, Wnt signaling for KDM4B, targeting pluripotency factors for KDM4C, and hypoxia-inducible factor 1 signaling for KDM4D [ 23 ]. Although the cellular functions of KDM4 demethylases are yet to be fully characterized, studies show that the demethylation of, for example, H3K9me3 at promoter regions, correlates with the activation of associated genes [ 80 ].…”
Section: Inhibitors Of Jmjc Domain–containing Lysine Demethylasesmentioning
confidence: 99%
“…Dysregulation of several KDMs has also been implicated in diseases including cancer and inflammation [ 15 , 20 ]. The histone methylation states (e.g., Kme0 to Kme3) can be linked to unique biological activities [ 21 ] and the potential signaling mechanisms and biological pathways involved in diseases for each KMT family member have been summarized in recent reviews [ 20 , 22 , 23 ]. Therefore, this review focused on the lysine demethylase family.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Unlike acute inflammation, chronic inflammation could cause cancer due to uncontrolled cell proliferation and reduced DNA repair. [4][5][6] Inflammation plays a vital role in different pathological diseases; on the other side, cancer development involves a multi-step process. A better understanding of inflammatory pathways and the molecular mechanisms that lead to cancer contributes to improved prevention and treatment of inflammatory disease.…”
Section: Introduction 1inflammationmentioning
confidence: 99%
“…Apart from this, inflammation is also induced by chemicals and microbial agents [3] . Unlike acute inflammation, chronic inflammation could cause cancer due to uncontrolled cell proliferation and reduced DNA repair [4–6] . Inflammation plays a vital role in different pathological diseases; on the other side, cancer development involves a multi‐step process.…”
Section: Introductionmentioning
confidence: 99%